2019
DOI: 10.5937/ffr1901051m
|View full text |Cite
|
Sign up to set email alerts
|

Physical traits and nutritional quality of selected Serbian maize genotypes differing in kernel hardness and colour

Abstract: Physical quality traits (1000-kernel weight, density, milling response and soft endosperm portion), basic chemical (starch, protein, oil, cellulose and ash) and amino acids composition of ten ZP maize genotypes differing in kernel hardness and colour were studied. The objectives of this study were to characterize differences in ZP maize genotypes regarding to various physical traits and nutritional quality parameters such as basic chemical and amino acid composition and the data was correlated to find the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
6
3
0
Order By: Relevance
“…to the values obtained in other studies (Peplinski et al, 1992;Blandino et al, 2010;Milašinović Šeremešić et al, 2019). Most of the hybrids in this study had a 1,000 kernel weight between 300 and 350 g, while the weight of less than 300 g had 9% and higher than 350 g 21% of the tested hybrids.…”
Section: And 4)supporting
confidence: 84%
“…to the values obtained in other studies (Peplinski et al, 1992;Blandino et al, 2010;Milašinović Šeremešić et al, 2019). Most of the hybrids in this study had a 1,000 kernel weight between 300 and 350 g, while the weight of less than 300 g had 9% and higher than 350 g 21% of the tested hybrids.…”
Section: And 4)supporting
confidence: 84%
“…In a study conducted by Milenković et al (2014), 1000-kernel mass of the investigated lines ranged from 311.3 to 352.65 g. Somavat et al (2016) found that 1000-kernel mass of some differently coloured dent maize kernels, such as blue maize, is lower than the same parameter of yellow and red kernel maize. The test mass of popcorn hybrid ZP 611k kernel was higher than in all tested lines (886.40±6.28 kg m -3 ), as well as the absolute mass of the standard hybrid ZP 633 (303.81±2.79 g), which is in accordance with studies of ZP maize hybrids previously published (Milašinović-Šeremešić et al 2019;Milašinović-Šeremešić et al 2018;Semenčenko, 2013). Test mass is also a valuable indicator of maize grain quality, it is the oldest and easily measurable standard.…”
Section: Resultssupporting
confidence: 90%
“…Protein content results are in accordance with findings of Milenković et al (2014). Results of kernel the chemical composition are in accordance with results of the studies previously conducted in the Maize Research Institute (Milašinović Šeremešić et al, 2019, Semenčenko et al, 2015a, 2015b.…”
Section: Fig 1 Milling Response Of the Investigated Inbred Lines Andsupporting
confidence: 89%
See 1 more Smart Citation
“…Kernel hardness and vitreousness are highly associated with physical traits and significantly correlated with technological value and end usage of maize. The parameters are strongly determined by genotype (Radosavljević et al, 2000;Milašinović-Šeremešić et al, 2019). Kernel vitreousness, which refers to the ratio of vitreous (hard) to floury (soft) endosperm, is a major physical trait that influences hardness, post-harvest resistance to insects and fungi, rate of starch digestibility, and semolina yield for food production (Gayral et al, 2015).…”
Section: Introductionmentioning
confidence: 99%